2018
DOI: 10.1139/cjz-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Increased diet breadth of little brown bats (Myotis lucifugus) at their northern range limit: a multimethod approach

Abstract: Increased diet breadth of little brown bats (Myotis lucifugus) at their northern range limit: a multi-method approachThe distribution of small mammals is constrained by extreme environmental 24 demands and variable food supplies that are commonly incurred at northern latitudes. 25Little brown bats (Myotis lucifugus, Le Conte, 1831) are at the northwestern limits of 26 their range in Alaska, where environmental demands are higher and prey availability is 27 more seasonal than elsewhere in their range. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…In concordance with dietary studies on insectivorous bats, we also revealed a high frequency of lepidopteran and Dipteran species in the diets of the sampled species (Clare et al, ; Shively et al, ; Vesterinen et al, ). In fact, combined, these two orders constitute the majority of all predation records in the whole study, regardless of the data type (read counts, frequency, or presence/absence).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In concordance with dietary studies on insectivorous bats, we also revealed a high frequency of lepidopteran and Dipteran species in the diets of the sampled species (Clare et al, ; Shively et al, ; Vesterinen et al, ). In fact, combined, these two orders constitute the majority of all predation records in the whole study, regardless of the data type (read counts, frequency, or presence/absence).…”
Section: Discussionsupporting
confidence: 89%
“…Here, we unravel the resource partitioning of five resident vesper bats in southwestern Finland through deep dietary analysis, including prey species identification, an estimate for prey body size and temporal changes in diet using fecal DNA barcoding. At high northern latitudes, the distribution of bats is constrained by extreme environmental demands and prey availability is more seasonal than elsewhere in their range (Clare et al, ; Shively & Barboza, ; Shively, Barboza, Doak, & Jung, ). The ranges of these five species ( Eptesicus nilssonii [Keyserling & Bläsius, 1839], Myotis daubentonii [Kuhl, 1817], M. mystacinus [Kuhl, 1817], M. brandtii [Eversmann, 1845], and Plecotus auritus [Linnaeus, 1758]) show considerable overlap, suggesting that trophic resource partitioning is important in supporting the species in Fennoscandia.…”
Section: Introductionmentioning
confidence: 99%
“…, Shively et al. ). Other studies have found that insect biomass declined with increasing housing density, causing reduced foraging rates by bats in urban areas (Geggie and Fenton , Threlfall et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent work suggests that little brown bats at high latitudes do not rely on aerial prey in times of scarcity; rather, they will switch to gleaning terrestrial prey (e.g., spiders), a unique strategy among northern populations (Kaupas and Barclay , Shively et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation